(untitled) (Kronika Bydgoska, 2010)
The primary objective of this work was to present the history of two hospitals in Bydgoszcz, which were established in the 16th century. Many aspects touched on aimed at showing the local hospital system in the context of its influence on the local ecclesiosphere and the residents of the city on the Brda River. Presented were also, among others, the existential conditions prevailing in the hospitals and the practices that used to set the rhythm of the inmates’ life every day.